M o d u l a t i o n o f a d h e s i o n: d e p e n d e n t s i g n a l l i n g b y CK2 a n d i t s a s s o c i a t e d r e g u l a t o r s i n h o s c c c e l l s - Buthelezi, Sandile (My University, 2022)
CK2 introduces a supplementary regulatory influence on proliferative pathways, aberrant in oncogenic signalling. This, with the nodal positioning of PKB in proliferative signalling, necessitated the elucidation of signalling routes employed by the EGFR overexpressing oesophageal squamous carcinoma cells. Furthermore, differential regulation of the PI3K/PKB proliferative signalling axis, within the series of oesophageal carcinoma cells, potentiates significant implications for the resistance to therapeutic interventions. Western blotting and densitometry were used to measure changes in pathway-specific protein concentrations in response to stimulation by EGF, or specific blockade of signalling intermediates. Whilst proliferation assays were conducted using the MTT method. The activation of EGFR significantly increased the concentration of CK2 in a time-dependent manner in the SNO oesophageal carcinoma cells (p < 0,05) and A431 epidermoid carcinoma cells (control) (p < 0,05) only, while phospho-GSK3β levels were only significantly increased SNO cells (p < 0,05). Concurrent blockade of CK2 function (TBB) with the specific inhibition of PI3K (LY294002) led to decreased abundance of active PKB and phospho-GSK3β concentrations in the WHCO1, SNO and A431 cell lines. However, this dual inhibition in the WHCO3 cells produced an increase in phospho-GSK3β in the absence of phospho-PKB. Strikingly, in the WHCO3 cells, there was a depression of phospho-GSK3β levels when CK2 was abrogated concurrently with specific RSK inhibition (BI-D1870) – this is further supported by a 46% loss of proliferative activity (p < 0,05) when WHCO3 cells were challenged with the RSK inhibitor, concurrent with EGF stimulation. Such changes were less noticeable in the WHCO1 and SNO cell lines, indicative of complementary routes to effect GSK3β inhibition in the WHCO1 and SNO cells. These data demonstrate that the WHCO1 and SNO cells (like the A431 cells) primarily employ the PI3K-PKB signalling axis to inhibit GSK3β. In contrast, the WHCO3 use a RSK-associated pathway which is chaperoned by CK2. Together, these differentially regulated EGFR-derived cues depend on the influence of CK2 to effect inhibition of GSK3β, for proliferative signalling in the oesophageal cancer cells. While the salvage pathway involving the ERK/RSK axis being used by cells v that maintain low levels of active PKB. Finally, for these and other reasons CK2 is an important regulator of both the PI3K/PKB and ERK/RSK proliferative pathways in adherent HOSCC cells and it may enhance the resistance to therapeutic interventions that are dependent on PKBA thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy in Geography to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2022
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy in Molecular and Cell Biology to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022